Evaluating the benefits of a rapid access chest pain clinic in Australia. Issue 7 (18th February 2019) - Black, James Andrew; Cheng, Kevin; Flood, Jo‐Anne; Hamilton, Garry; Parker, Serena; Enayati, Anees; Khan, Faisal S; Marwick, Tom
Abstract: Objectives: To compare the outcomes and safety of a rapid access chest pain clinic (RACPC) in Australia with those of a general cardiology clinic. Design: Prospective comparison of the outcomes for patients attending an RACPC and those of historical controls. Setting: Royal Hobart Hospital cardiology outpatient department. Participants: 1914 patients referred for outpatient evaluation of new onset chest pain (1479 patients seen in the RACPC, 435 patients previously seen in the general cardiology clinic). Main outcome measures: Service outcomes (review times, number of clinic reviews); adverse events (unplanned emergency department re‐attendances at 30 days and 12 months; major adverse cardiovascular events at 12 months, including unplanned revascularisation, acute coronary syndrome, stroke, cardiac death). Results: Median time to review was shorter for RACPC than for usual care patients (12 days [IQR, 8–15 days] v 45 days [IQR, 27–89 days]). All patients seen in the RACPC received a diagnosis at the first clinic visit, but only 139 patients in the usual care group (32.0%). There were fewer unplanned emergency department re‐attendances for patients in the RACPC group at 30 days (1.6% v 4.4%) and 12 months (5.7% v 12.9%) than in the control group. Major adverse cardiovascular events were less frequent among patients evaluated in the RACPC (0.2% v 1.4%). Conclusions: Patients were evaluated more efficiently in the RACPC than in a traditional cardiology clinic, and their subsequent rates of emergency department re‐attendances and adverse cardiovascular events were lower.